Responsibilities and Legal Protection for Notaries in Civil Procedure for Deeds That Have Been Issued - Zaini, Zulfi Diane; Dolores, Margareta (Journal of Education Technology Information Social Sciences and Health, 2024)
Notaries as Public Officials are given the authority by the state to declare the existence of a legal relationship between the parties in a deed which directly records the agreement clauses of the promising parties. The promises stated in the deed are a reflection of the sincere wishes of the parties. An Authentic Deed is a means of evidence for the parties to legally prove a legal event in both civil and criminal cases. The formulation of the problem in this research is how the notary is held civilly responsible for the deed issued and what is the legal protection for notaries regarding the deeds they make regarding the civil liability of notaries. The research method used in this research is a normative juridical approach and an empirical approach. Secondary data is data obtained through library research, such as literature books and scientific works related to research problems. Secondary data consists of 3 (three) Legal Materials, namely, Primary, Secondary and Tertiary Legal Materials. Prime data is data obtained from research results in the field directly on research objects (field research) carried out by means of direct observation and interviews. The results of this research show that the Notaries are obliged to be held accountable for their actions by being subject to civil sanctions in the form of reimbursement of costs or compensation to parties who suffer losses due to unlawful acts committed by the Notary. However, before the Notary is subject to civil sanctions, the Notary must first be able to prove that there has been a loss resulting from the Notary's unlawful actions against the parties, and that between the losses suffered and the Notary's unlawful actions there is a causal relationship, as well as the unlawful actions or negligence. caused by errors that can be accounted for by the Notary concerned. And then, then the legal protection for Notaries for the deeds they make regarding the civil liability of Notaries is the establishment of a Supervisory Board based on Articles 70 and 73 of the Notary Position Law. In the event that a Notary is suspected of committing a violation by making a Deed that is detrimental to the parties, then there are processes and procedures before the Notary can attend the trial which must be approved by the Notary Honorary Council, so that investigators do not arbitrarily summon the Notary to appear before the trial, one of which is to maintain the honor and dignity of the Notary and protect the notary's oath which must maintain the confidentiality of the Deed that has been made.